IMPLEMENTASI KEBIJAKAN INDEKS DESA MEMBANGUN (IDM) DI DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN SUMEDANG - Indriani, Ari Fitri (JRPA - Journal of Regional Public Administration, 2025)
The implementation of the Building Village Index policy needs to be carried out to measure the status of progress and independence of a village. This study aims to find out the extent to which the Implementation of the Building Village Index (IDM) Policy at the Sumedang Regency Community and Village Empowerment Office has been implemented. The research method used in the research is the Qualitative Research method. The sampling technique used is Purposive Sampling. The informants in this study are the Head of Village Government, Functional Position of Policy Analyst, Young Expert in the Field of P2LKD, Policy Analyst in the Field of Village Government, and Implementer of the Village Government Sector. The data collection techniques used are literature studies and field studies consisting of observation, interviews, documentation, and triangulation. Meanwhile, the data processing procedures in this study are data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the research, data analysis was carried out and it was concluded that the implementation of the Building Village Index (IDM) Policy at the Sumedang Regency Community and Village Empowerment Office has been implemented quite well, but there are several shortcomings. This can be seen from several factors such as lack of village understanding, limited human resources in monitoring, evaluation, and socialization, villages not listening to the information conveyed, there are still villages that are not aware of the importance of community input, and budget limitations. Based on the results of the research, there are several suggestions, including the need for a more effective communication strategy between DPMD and villages in conveying information, evaluation and adjustment of the number of implementers by DPMD by considering the area handled, and improving the quality and availability of facilities and infrastructure.